The Implementation Of School Regulations In Developing Students’ Discipline Character In An Elementary School - Muhammad Majdi; Raudatul Jinan; Risya Norhasanah (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
School regulations constitute binding rules for all members of the school community to support the teaching and learning process. Discipline character education, derived from the term “disciplina,” refers to mental and moral training aimed at fostering obedience to rules based on self-awareness. Discipline offers several benefits, including the development of positive habits, the enhancement of independence, and the cultivation of responsibility. Using a qualitative approach, this study involved students of SDN 1 Sei Rukam 1 as the research subjects in examining the implementation of school regulations in developing discipline character. The findings indicate that the implementation of school regulations in fostering discipline character education at SDN 1 Sei Rukam, Pugaan District, Tabalong Regency, has been carried out effectively. This study is expected to contribute to improving students’ disciplinary attitudes.